Development of stretch flangeable ferrite–bainite grades through thin slab casting and rolling. Issue 4 (3rd March 2016) - Mukherjee, M.; Chintha, A.R.; Kundu, S.; Misra, S.; Singh, J.; Bhanu, C.; Venugopalan, T.
Abstract : The focus towards the design of light environment friendly fuel efficient vehicles has led to an increase in the demand for high strength steels. As it is true for any developing country, the extra challenge for Indian steel industries is to produce such high strength steels at minimum cost. The aim of the present work was to develop two high strength steel grades with minimum tensile strengths of 540 and 590 MPa, in combination with good ductility and stretch flangeability, through the thin slab casting and rolling route. The present paper describes the alloy and process design methodology used for achieving the target properties. Several mill trials were taken to test the proposed design, wherein the target microstructure and mechanical properties were successfully achieved.